2016
DOI: 10.1051/0004-6361/201527792
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of solar radio and extreme ultraviolet synoptic limb charts during the present solar maximum

Abstract: Aims. The present solar cycle is particular in many aspects: it had a delayed rising phase, it is the weakest of the last 100 yrs, and it presents two peaks separated by more than one year. To understand the impact of these characteristics on the solar chromosphere and coronal dynamics, images from a wide wavelength range are needed. In this work we use the 17 GHz radio continuum, which is formed in the upper chromosphere and the extreme ultraviolet (EUV) lines 304 and 171 Å, that come from the transition regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Whereas, during the minimum, the frequency of flares and CMEs decreases and coronal hole tend to form at near the poles. There are several reports on various phenomena depending on the phase of the solar cycle, such as polar magnetic fields, polar crown filaments, surges near the poles, faculae, and so on (Selhorst et al 2003;Svalgaard et al 2005;Gopalswamy et al 2012;Shimojo 2013;Svalgaard & Kamide 2013;Altrock 2014;Silva et al 2016). For instance, the polar field reversal and flux migration to the poles are considered an indicator of the following solar maximum (Svalgaard & Kamide 2013) which is consistent with the dynamo model (Babcock 1961).…”
Section: Introductionmentioning
confidence: 66%
“…Whereas, during the minimum, the frequency of flares and CMEs decreases and coronal hole tend to form at near the poles. There are several reports on various phenomena depending on the phase of the solar cycle, such as polar magnetic fields, polar crown filaments, surges near the poles, faculae, and so on (Selhorst et al 2003;Svalgaard et al 2005;Gopalswamy et al 2012;Shimojo 2013;Svalgaard & Kamide 2013;Altrock 2014;Silva et al 2016). For instance, the polar field reversal and flux migration to the poles are considered an indicator of the following solar maximum (Svalgaard & Kamide 2013) which is consistent with the dynamo model (Babcock 1961).…”
Section: Introductionmentioning
confidence: 66%
“…Nevertheless, they are frequently associated with the location of increased unipolar magnetic regions underlying the coronal holes (Gopalswamy et al 1999;Brajša et al 2007;Selhorst et al 2010). This association was reinforced by Oliveira e Silva et al (2016), who analyzed the polar behavior between 2010 and 2015 and found a good correspondence between the presence of coronal holes and polar brightening at 17 GHz.…”
Section: Introductionmentioning
confidence: 88%
“…The purpose of this work is to model the emission of the 17 GHz polar bright patches, which are frequently observed in the NoRH maps in association with coronal holes (Gopalswamy et al 1999;Selhorst et al 2003;Oliveira e Silva et al 2016). The simulations were based on the temperature and density distributions proposed in the SSC atmospheric model (Selhorst et al 2005a), with modifications to include a coronal hole atmospheric model and magnetic loops as the sources of the radio bright patches.…”
Section: Discussionmentioning
confidence: 99%
“…• of latitude are not able to reproduce the intense bright patches observed in the NoRH maps (Selhorst et al 2005b) and the presence of coronal holes reduce the expected limb brightening at 17 GHz (Figure 4), other solar features should be acting inside the coronal holes to increase their brightness temperature at 17 GHz (Gopalswamy et al 1999;Oliveira e Silva et al 2016). To simulate the observed 17 GHz bright patches, we introduced small magnetic loops inside coronal hole regions (Figure 2).…”
Section: Polar Bright Patchesmentioning
confidence: 99%
See 1 more Smart Citation